جماليات التكوينات الخطية والعناصر التشكيلية في التصميم الفني في كسوة الكعبة المشرفة - Duaa Mohammed Alashari (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
The art of Arabic calligraphy with its artistic and plastic elements and vocabulary has a key role in highlighting the aesthetics of the covering of the Kaaba, in addition to the fact that all the plastic elements in the design of the structure of the linear formations result from the organization of linear relationships on the surface of the covering fabric, which are intertwined and intertwined in all formations and linear structures in the dress of the Kaaba. Therefore, this study aims to analyze the aesthetic relationships between the linear structural elements and the plastic artistic elements present in the design of the covering of the Kaaba according to an analytical artistic vision. The method used in this study is the content analysis method, which is an applied field study based on a careful and detailed analysis of the compositional, plastic and design elements within the dress of the Kaaba. The study concluded that the linear and artistic plastic elements had a prominent role in enhancing the aesthetics of the covering of